Genetic basis of the oil biosynthesis in ultra-high-oil maize grains with an oil content exceeding 20% - Luo, Meijie; Lu, Baishan; Shi, Yaxing; Zhao, Yanxin; Liu, Junling; Zhang, Chunyuan; Wang, Yuandong; Liu, Hui; Shi, Yamin; Fan, Yanli; Xu, Li; Wang, Ronghuan; et al. (Frontiers in Plant Science, 2023)
Vegetable oil is an important part of the human diet and has multiple industrial uses. The rapid increase in vegetable oil consumption has necessitated the development of viable methods for optimizing the oil content of plants. The key genes regulating the biosynthesis of maize grain oil remain mostly uncharacterized. In this study, by analyzing oil contents and performing bulked segregant RNA sequencing and mapping analyses, we determined that su1 and sh2-R mediate the shrinkage of ultra-high-oil maize grains and contribute to the increase in the grain oil content. Functional kompetitive allele-specific PCR (KASP) markers developed for su1 and sh2-R detected su1su1Sh2Sh2, Su1Su1sh2sh2, and su1su1sh2sh2 mutants among 183 sweet maize inbred lines. An RNA sequencing (RNA-seq) analysis indicated the genes differentially expressed between two conventional sweet maize lines and two ultra-high-oil maize lines were significantly associated with linoleic acid metabolism, cyanoamino acid metabolism, glutathione metabolism, alanine, aspartate and glutamate metabolism, and nitrogen metabolism. A bulk segregant analysis sequencing (BSA-seq) analysis identified another 88 genomic intervals related to the grain oil content, 16 of which overlapped previously reported maize grain oil-related QTLs. The combined analysis of BSA-seq and RNA-seq data enabled the identification of candidate genes. The KASP markers for GRMZM2G176998 (putative WD40-like beta propeller repeat family protein), GRMZM2G021339 (homeobox-transcription factor 115), and GRMZM2G167438 (3-ketoacyl-CoA synthase) were significantly related to the maize grain oil content. Another candidate gene GRMZM2G099802 (GDSL-like lipase/acylhydrolase) catalyzes the final step of the triacylglycerol synthesis pathway and was expressed at significantly higher levels in the two ultra-high-oil maize lines than in the two conventional sweet maize lines. These novel findings will help clarify the genetic basis of the increased oil production in ultra-high-oil maize lines with grain oil contents exceeding 20%. The KASP markers developed in this study may be useful for breeding new high-oil sweet maize varieties.